Endoscopic Ultrasound-Guided Random Omental Fine Needle Aspiration: A Novel Technique for the Diagnosis of Peritoneal Carcinomatosis - Pradeep Kumar Siddappa; Neha Jain; Naveen K. Agarwal; Monika Jain; Gurwant Singh Lamba (Korean Society of Gastrointestinal Endoscopy, 2020)
Background/Aims Diagnostic abdominal paracentesis has been described in literature to have variable sensitivity of 50%-75% for the detection of peritoneal carcinomatosis (PC). We believe that random needle aspirates from the omentum, even in the absence of obvious deposits by endoscopic ultrasound (EUS), could prove malignancy in patients with PC. Methods Consecutive patients who underwent EUS for diagnosis and staging of cancer and found to have ascites were included after obtaining informed consent. EUS-guided fine needle aspiration (EUS-FNA) from random sites in the omentum was performed through the transgastric route using a linear echoendoscope. Results Fifty-four patients underwent EUS during October 2015 to April 2017 for detection, staging, or FNA of a suspected malignant lesion. Ascites was seen in 17 patients and 15 patients who fulfilled the criteria were included. The procedure was successful in all patients. Cytology was suggestive of malignancy in 12 (80%) but not suggestive of malignancy in 3 (20%) patients. Three patients who tested negative had hyperbilirubinemia with biliary obstruction. Their ascitic fluid analysis result was also negative. Conclusions Random FNA of the omentum in patients with malignancy-related ascites is highly effective in the diagnosis of PC and could be employed during EUS evaluation of malignancies.